The Reduplication Process of Balantak Language: A Minority Austronesian Language of Eastern Sulawesi - Pamolango, Valentino; Young Ho , Cho (Investigationes Linguisticae, 2020)
Indonesia has many local languages. One of the local languages used in Indonesia is Balantak language. It is used by people who live in 5 (five) sub-districts in Banggai Regency, Central Sulawesi. In Balantak language, there are a number of words which are formed by using reduplication. Reduplication is found in many languages but is quite diverse as a process and in its. Due to reduplicated words in Balantak language, the writers are interested in analyzing the problem statement about: What are the forms of reduplicated words in Balantak language? Reduplication is the repetition of an entire word or part of the word. According to Haspelmath and Sims (2010), reduplications are a very common morphological operation, whereby part of the base orthe complete base is copied and attached to the base (either preceding or following it). In Balantak language both forms of reduplication are found full reduplication and partial reduplication, and each form consists of various kind of words.